2016
DOI: 10.1063/1.4961258
|View full text |Cite
|
Sign up to set email alerts
|

Comparative stereodynamics in molecule-atom and molecule-molecule rotational energy transfer: NO(A2Σ+) + He and D2

Abstract: We present a crossed molecular beam scattering study, using velocity-map ion-imaging detection, of state-to-state rotational energy transfer for NO(A(2)Σ(+)) in collisions with the kinematically identical colliders He and D2. We report differential cross sections and angle-resolved rotational angular momentum polarization moments for transfer of NO(A, v = 0, N = 0, j = 0.5) to NO(A, v = 0, N' = 3, 5-12) in collisions with He and D2 at respective average collision energies of 670 cm(-1) and 663 cm(-1). Quantum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(38 citation statements)
references
References 57 publications
3
35
0
Order By: Relevance
“… 15 Luxford et al reported the state-to-state DCSs and angular resolved rotational angular momentum polarization moments for collisions of electronically excited NO( A 2 Σ) with D 2 . 16 Recently, de Jongh et al studied the DCS of NO + He and NO + ortho -D 2 with very high resolution as a function of the collision energy using a Stark decelerator, resolving diffraction oscillations in the angular distributions. Due to the larger size of D 2 , the differences in angular spacing between individual diffraction peaks were observed.…”
Section: Introductionmentioning
confidence: 99%
“… 15 Luxford et al reported the state-to-state DCSs and angular resolved rotational angular momentum polarization moments for collisions of electronically excited NO( A 2 Σ) with D 2 . 16 Recently, de Jongh et al studied the DCS of NO + He and NO + ortho -D 2 with very high resolution as a function of the collision energy using a Stark decelerator, resolving diffraction oscillations in the angular distributions. Due to the larger size of D 2 , the differences in angular spacing between individual diffraction peaks were observed.…”
Section: Introductionmentioning
confidence: 99%
“…We observed quantitative agreement between experiment and theory for NO(A) + He, and very good agreement for NO(A) + Ar. 25,27 There are larger discrepancies between QS calculations and experiment for NO(A) + Ne. 23,26 In particular, we observe a strong forward scattered peak in the 0-101 range in the experimental DCSs for a wide range of final rotational states, which is not reproduced by QS calculations.…”
Section: Introductionmentioning
confidence: 99%
“…However, following our initial demonstration of the combination of optical state preparation of NO(A) with crossed molecular beams and VMI detection, [20][21][22] we have performed a series of systematic experimental and theoretical studies of rotationally inelastic collisions of NO(A). [23][24][25][26][27] In these experiments we have measured both DCSs and angle-resolved rotational alignment moments for the NO(A) + He, Ne and Ar systems. We observed quantitative agreement between experiment and theory for NO(A) + He, and very good agreement for NO(A) + Ar.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Recently, the DCSs, as well as the rotational polarization moments, have been measured for electronically excited NO(A 2 Σ + ) colliding with He and D 2 . 5 The NO-He system has been the subject of several highlevel ab initio studies and its PES is well-known. [6][7][8] The scattering cross sections computed with these PESs are generally in very good agreement with experimentally determined cross sections.…”
Section: Introductionmentioning
confidence: 99%